FORMULATING THEORIES OF DAKWAH STUDIES - Nur Syam (Sayyid Ali Rahmatullah Tulungagung State Islamic University, 2019)
This paper examines the contribution of sociology to the making of dakwah studies. From epistemological point of view, dakwah studies develops through five elements: factors, systems, interpretative, developmentalism and participatory. These five elements can be developed based on sociological theories. Through a sociological approach, dakwah studies will be able to contribute to general discussion on the sociology of Muslim societies. The article further argues the inclusion of social science is a pattern of knowledge development based on the integration of science, namely the phenomenon of dakwah as an object of study, while utilizing other social science as approaches.